Desain Bahan Ajar Handout QR Code Materi Kehidupan Mesolitik Gua Lawa Sampung - Nurul Nurul Hidayati; Blasius Suprapta; Wahyu Djoko Sulistyo (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2021)
The design of QR Code handout teaching materials is the concept of combining the use of smartphones with teaching materials that contain material about the history of the mesolithic life of Lawa Sampung Cave. The purpose of designing this QR Code handout is to provide teaching materials as a companion book to make it easier for students to understand the material of Mesolithic Life in Lawa Cave. This is based on the finding that students do not understand the material of the mesolithic era and the limited learning resources used. The hypothesis of this study is that the design of QR Code handout teaching materials is effectively used to support the learning process. Researchers in conducting research using research and development designs. The instrument used to measure the research variables was a questionnaire given to class X students. Research respondents The instrument used was 40 students. The research was conducted at SMAN 1 Sampung Ponorogo, East Java. Data analysis techniques used qualitative and quantitative data. Based on the results of the analysis, it can be concluded that teaching materials that can be accessed via a smartphone are needed so that they can support student learning.